Analysis of learning difficulties of students in regular and sports-specific classes (SSC) on cell material - Arafah, Nailatul; Sudrajat, Ahmad Kamal (Universitas Negeri Yogyakarta, 2026)
This study aims to identify and describe the forms and levels of students’ learning difficulties in cell material at SMA Negeri 2 Playen, analyze the causal factors, and determine the efforts students make to overcome them. This descriptive study uses a quantitative approach reinforced by qualitative data. The subjects of the study were 11th-grade biology students and 11th-grade biology teachers. Data were collected through questionnaires, interviews, and document analysis, using instruments that had been tested for content and construct validity and for Cronbach’s Alpha reliability. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the Miles Huberman model. The results showed that learning difficulties included understanding, remembering, focusing, differentiating, and drawing, with an SSC student’s internal factors difficulty level of 2.41 (high category). The causes differed between regular and SSC classes. Student efforts included searching for additional materials, re-understanding, summarizing, memorizing, asking others for help, and seeking tutoring. Teachers are advised to try other methods, such as the Team Game Tournament (TGT). This study provides teachers with insights to address student learning difficulties in both regular and sports classes.